𝛽-Thalassemia: HiJAKing Ineffective Erythropoiesis and Iron Overload - Luca Melchiori; Sara Gardenghi; Stefano Rivella (Advances in Hematology)
𝛽-thalassemia encompasses a group of monogenic diseases that have in common defective synthesis of 𝛽-globin. The defects involved are extremely heterogeneous and give rise to a large phenotypic spectrum, with patients that are almost asymptomatic to cases in which regular blood transfusions are required to sustain life. As a result of the inefficient synthesis of 𝛽-globin, the patients suffer from chronic anemia due to a process called ineffective erythropoiesis (IE). The sequelae of IE lead to extramedullary hematopoiesis (EMH) with massive splenomegaly and dramatic iron overload, which in turn is responsible for many of the secondary pathologies observed in thalassemic patients. The processes are intimately linked such that an ideal therapeutic approach should address all of the complications. Although 𝛽-thalassemia is one of the first monogenic diseases to be described and represents a global health problem, only recently has the scientific community started to focus on the real molecular mechanisms that underlie this disease, opening new and exciting therapeutic perspectives for thalassemic patients worldwide.